Elevated Bilirubin-to-Albumin Ratio as a Predictor of Mortality in Liver Diseases - Shah, Nazir; Haleem, Muhammad; Mahmood, Nasir; Abdullah, Syed (Journal of Postgraduate Medical Institute, 2025)
Objective; The objective of this study is to evaluate the prognostic accuracy of the bilirubin-to-albumin ratio for predicting mortality in patients with chronic or acute liver disease presenting with acute liver failure. Methodology: This was a multicenter descriptive cross-sectional study which was performed in the Department of General Medicine, Hayatabad Medical Complex, Department of Pediatrics, Lady Reading Hospital, Peshawar, and Department of Medicine, District Headquarters Teaching Hospital, Haripur, Pakistan. The study duration was about 3 months extending from 10th August 2024 to 22nd December 2024. We consecutively collected 69 patients of both genders with chronic or acute liver diseases presenting with liver failure as evidenced by hepatic encephalopathy, increased prothrombin time and INR. The patients were recruited from the wards and ICUs of the respective hospitals. The underlying etiology of liver disease was identified, and related blood tests including the serum bilirubin and albumen, were performed within the first 24 hours of admission at the main laboratories of the respective hospitals. Bilirubin-to-albumin (B/A) ratio was calculated by dividing the total bilirubin (mg/dl) by the serum albumin (gm/dl) at the time of admission. The normal range of the bilirubin albumen ratio (B/A) is 0.01–0.2, while levels above 0.7 were considered significant and classified as elevated in this study. All patients were monitored throughout their hospital stay and for three months post-discharge. Mortality within this follow-up period was assessed. Results; The total number of patients was 69 and the age range was from 1 to 62 years with mean age of 43.130±4.90 years and mean duration of liver disease was 19.985±4.55 months. An elevated bilirubin/albumin (B/A) ratio was diagnosed in 29(42%) and the total mortality was seen in 33(47.8%). Bilirubin/Albumin (B/A) ratio showed sensitivity of 66.7%, specificity 80.5%, diagnostic accuracy 74%, with positive predictive value 75.9% and negative predictive value of 72.5%. Conclusion; Results from the present study showed that a normal or near normal Bilirubin/Albumin (B/A) ratio determined on admission predicts good prognosis regarding the survival of patients with acute liver failure. Based on our preliminary data, a future study with a large number of patients would be required to adequately power a multivariate analysis.